In Vitro Effects of Homeopathic Drugs on Cultured Escherichia coli - Pannek, Jürgen; Kurmann, Carmen; Imbach, Esther; Amsler, Felix; Pannek-Rademacher, Susanne (Homeopathy, 2018)
Background Recurrent urinary tract infections (UTIs) are one of the most common morbidities in persons with neurogenic lower urinary tract dysfunction (NLUTD). Repetitive antibiotic treatment increases the risk of selecting multi-resistant bacteria. Homeopathic treatment has been reported to be effective in these patients. The mechanism of action, however, has not been clarified. Recently, a direct bactericidal effect of homeopathic remedies was shown. Such an effect is not in accordance with the general principles of homeopathy. To test this paradigm, we assessed the in vitro effects of homeopathic drugs on Escherichia coli derived from patients with NLUTD.Methods E. coli bacteria were harvested from 28 consecutive urine cultures. Standard antibiotic resistance testing and simultaneous resistance testing to homeopathic drugs (Apis mellifica, Cantharis, Causticum hahnemanni, Staphysagria, Nux vomica, Berberis vulgaris, and Lycopodiumclavatum) in high (C30) potency were performed.Results No significant inhibitory effect of any of the tested homeopathic drugs on any E. coli population could be found, irrespective of their sensitivity to antibiotic treatment.Conclusion Based on our results, effects of homeopathic treatment of UTI are not based on direct bactericidal or bacteriostatic effects. These findings are in concordance with the hypothesis that homeopathy is based on host effects: for example, activation of the immune system, rather than effects on pathogens.
Keywords: urinary tract infection; microbiology; antibiotics